Experimental implantoplasty outcomes correlate with fibroblast growth in vitro - Mehrnaz Beheshti Maal; Stig Aanerød Ellingsen; Janne Elin Reseland; Anders Verket (BMC, 2020)
Abstract Background Implantoplasty is an option in peri-implantitis treatment, but little is known about the effect on the soft tissue. The aim of the study was to characterize surface roughness following experimental implantoplasty and to examine its effect on human fibroblast growth and secretion of selected proteins. Methods Titanium grade IV coins were mechanically treated with six different rotating bur sequences; diamond burs or carbide burs alone, or followed by either Arkansas stone bur or silicone burs. Machined and rough-surface sandblasted, acid-etched (SLA) coins were used as control. The surface topography was characterized by scanning electron microscope and profilometer. Human gingival fibroblasts from two donors were cultured on the coins to quantify the effect on cell morphology, growth, and protein secretion by confocal microscopy and multiplex immunoassay. Results All surface roughness parameters were lower for the surfaces treated with experimental implantoplasty than for the SLA surface, and the sequence of carbide burs followed by silicone burs rendered the least rough surface of the test groups. The implantoplasty procedures changed the elemental composition of the titanium surface. High surface roughness showed a weak to moderate negative correlation to fibroblast growth, but induced a higher secretion of VEGF, IL-6 and MCP-3 to the cell medium compared to the least rough surfaces of the test groups. At day 30 fibronectin levels were higher in the SLA group. Conclusions The surface roughness following implantoplasty demonstrated a weak to moderate negative correlation with the growth of fibroblasts. The addition of Arkansas stone and silicon burs to the experimental implantoplasty bur protocol rendered an initial increase in fibroblast growth. Implantoplasty altered the elemental composition of the titanium surface, and had an effect on the fibroblast cytokine secretion and fibronectin levels.